2020
DOI: 10.3389/fpls.2019.01774
|View full text |Cite
|
Sign up to set email alerts
|

Deep Eutectic Solvent Pretreatment of Transgenic Biomass With Increased C6C1 Lignin Monomers

Abstract: The complex and heterogeneous polyphenolic structure of lignin confers recalcitrance to plant cell walls and challenges biomass processing for agroindustrial applications. Recently, significant efforts have been made to alter lignin composition to overcome its inherent intractability. In this work, to overcome technical difficulties related to biomass recalcitrance, we report an integrated strategy combining biomass genetic engineering with a pretreatment using a bio-derived deep eutectic solvent (DES). In par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Assessment of both strategies in sugarcane showed that HCHL was more efficient than UbiC, resulting in the production of 7.3% and 1.5% dry weight (DW) of 4-HBA glucosides in leaves and stems, respectively [26]. Moreover, analysis of lignin purified from Arabidopsis plants transformed with a HCHL gene showed the presence of 4-HBA and syringaldehyde units, as well as a reduction in the lignin degree of polymerization, which results in increases of biomass saccharification efficiency [27,28]. Therefore, the HCHL engineering strategy has the potential to bring two valuable traits in bioenergy crops, namely 'enhanced biomass deconstructability' and 'valueadded coproduct' .…”
Section: -Hydroxybenzoic Acidmentioning
confidence: 99%
“…Assessment of both strategies in sugarcane showed that HCHL was more efficient than UbiC, resulting in the production of 7.3% and 1.5% dry weight (DW) of 4-HBA glucosides in leaves and stems, respectively [26]. Moreover, analysis of lignin purified from Arabidopsis plants transformed with a HCHL gene showed the presence of 4-HBA and syringaldehyde units, as well as a reduction in the lignin degree of polymerization, which results in increases of biomass saccharification efficiency [27,28]. Therefore, the HCHL engineering strategy has the potential to bring two valuable traits in bioenergy crops, namely 'enhanced biomass deconstructability' and 'valueadded coproduct' .…”
Section: -Hydroxybenzoic Acidmentioning
confidence: 99%
“…27−29 These phenolic compoundbased DESs have been successfully applied to several biomass feedstocks. [19][20][21]30,31 In addition, the different molar ratios and combinations of lignin-derived DESs were compared to evaluate the pretreatment efficiency. Kim et al tested several phenolic compounds, including vanillin, catechol, 4-hydroxybenzyl alcohol, and p-coumaric acid synthesized with ChCl for DES formation and compared their biomass pretreatment performance.…”
Section: Introductionmentioning
confidence: 99%
“…Such C 6 C 1 lignin monomers act as "DP-reducers" that lead to shorter lignin polymers with higher reactivity towards chemical processing, resulting in improved pretreatment efficiency. 7,8 Another lignin engineering strategy involves the incorporation of monolignol conjugates (i.e., acylated monolignols) into lignin polymers to introduce chemically labile ester bonds. For example, heterologous expression of a feruloyl-CoA:monolignol transferase gene in hybrid poplar led to the incorporation of backbone-integrated ester linkages (i.e., "zip lignin"), which resulted in significantly improved saccharification yields following pretreatment under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Such C 6 C 1 lignin monomers act as “DP-reducers” that lead to shorter lignin polymers with higher reactivity towards chemical processing, resulting in improved pretreatment efficiency. 7,8…”
Section: Introductionmentioning
confidence: 99%